What Do I Do Now?: Tackling Higher Education Adaptive Leadership Challenges - Jill Channing (Academic Chairpersons Conference Proceedings, 2022)
The presenter and participants will discuss current trends, policy issues, and adaptive challenges influencing higher education institutions. Through discussions of research and case scenarios, participants will analyze adaptive leadership strategies and best practices for chairs to develop departmental cultures that are responsive to adaptive challenges.
Keywords: Adaptive leadership; adaptive challenges; organizational culture; academic leadership; competency/professional development